Olive mill wastewater detoxification by applying pH related fenton oxidation process - Vlyssides, AG; Loukakis, HN; Karlis, PK; Barampouti, EMP; Mai, ST (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2004)
Detoxification and degradation of olive mill wastewater (OMW) by Fenton's process along with chemical coagulation and precipitation was investigated. Experiments were carried out to investigate the effects of pH and treatment time on the COD, BOD5 and Total Phenolic Compounds (TPC) removal efficiency. The detoxification rate of OMW, after Fenton's process application, was evaluated from the considerable improvement of the COD/BOD5 ratio in effluents and TPC removal rate that was achieved in all cases. Keeping the experimental conditions constant (pH 2.5, 20 degreesC, initial addition of 3 g FeSO4 7H(2)O and 3 ml H2O2 (60%) per L OMW, oxidation time 2 hours), COD reduction was about 60%, and those of BOD5 about 40% and TPC almost 100%. From the overall results it can be concluded that the oxidation of OMW using Fenton's process followed by biological treatment is an effective and feasible detoxification methodology.